Are pine plantations valid tools for restoring Mediterranean forests? An assessment along abiotic and biotic gradients - Gómez-Aparicio, LORENA; Zavala, MIGUEL a; Bonet, Francisco J; Zamora, Regino (ECOLOGICAL APPLICATIONS, 2009)
The ecological impacts of forest plantations are a focus of intense debate, from studies that consider plantations as ``biological deserts{''} to studies showing positive effects on plant diversity and dynamics. This lack of consensus might be influenced by the scarcity of studies that examine how the ecological characteristics of plantations vary along abiotic and biotic gradients. Here we conducted a large-scale assessment of plant regeneration and diversity in plantations of southern Spain. Tree seedling and sapling density, plant species richness, and Shannon's (H') diversity index were analyzed in 442 pine plantation plots covering a wide gradient of climatic conditions, stand density, and distance to natural forests that act as seed sources. Pronounced variation in regeneration and diversity was found in plantation understories along the gradients explored. Low-to mid-altitude plantations showed a diverse and abundant seedling bank dominated by Quercus ilex, whereas high-altitude plantations showed a virtually monospecific seeding bank of Pinus sylvestris. Regeneration was null in plantations with stand densities exceeding 1500 pines/ha. Moderate plantation densities (500-1000 pines/ha) promoted recruitment in comparison to low or null canopy cover, suggesting the existence of facilitative interactions. Quercus ilex recruitment diminished exponentially with distance to the nearest Q. ilex forest. Richness and H' index values showed a hump-shaped distribution along the altitudinal and radiation gradients and decreased monotonically along the stand density gradient. From a management perspective, different strategies will be necessary depending on where a plantation lies along the gradients explored. Active management will be required in high-density plantations with arrested succession and low diversity. Thinning could redirect plantations toward more natural densities where facilitation predominates. Passive management might be recommended for low-to moderate-density plantations with active successional dynamics (e. g., toward oak or pine-oak forests at low to mid altitudes). Enrichment planting will be required to overcome seed limitation, especially in plantations far from natural forests. We conclude that plantations should be perceived as dynamic systems where successional trajectories and diversity levels are determined by abiotic constraints, complex balances of competitive and facilitative interactions, the spatial configuration of native seed sources, and species life-history traits.
Keywords: competition; environmental gradients; Facilitation; management strategy; Mediterranean forests; pine plantations; Regeneration; seed dispersal; species diversity; stand density

Are pine plantations valid tools for restoring Mediterranean forests? An assessment along abiotic and biotic gradients - Gómez-Aparicio, LORENA; Zavala, Miguel A.; Bonet, Francisco J.; Zamora, Regino (ECOLOGICAL APPLICATIONS, 2009)
The ecological impacts of forest plantations are a focus of intense debate, from studies that consider plantations as ``biological deserts{''} to studies showing positive effects on plant diversity and dynamics. This lack of consensus might be influenced by the scarcity of studies that examine how the ecological characteristics of plantations vary along abiotic and biotic gradients. Here we conducted a large-scale assessment of plant regeneration and diversity in plantations of southern Spain. Tree seedling and sapling density, plant species richness, and Shannon's (H') diversity index were analyzed in 442 pine plantation plots covering a wide gradient of climatic conditions, stand density, and distance to natural forests that act as seed sources. Pronounced variation in regeneration and diversity was found in plantation understories along the gradients explored. Low-to mid-altitude plantations showed a diverse and abundant seedling bank dominated by Quercus ilex, whereas high-altitude plantations showed a virtually monospecific seeding bank of Pinus sylvestris. Regeneration was null in plantations with stand densities exceeding 1500 pines/ha. Moderate plantation densities (500-1000 pines/ha) promoted recruitment in comparison to low or null canopy cover, suggesting the existence of facilitative interactions. Quercus ilex recruitment diminished exponentially with distance to the nearest Q. ilex forest. Richness and H' index values showed a hump-shaped distribution along the altitudinal and radiation gradients and decreased monotonically along the stand density gradient. From a management perspective, different strategies will be necessary depending on where a plantation lies along the gradients explored. Active management will be required in high-density plantations with arrested succession and low diversity. Thinning could redirect plantations toward more natural densities where facilitation predominates. Passive management might be recommended for low-to moderate-density plantations with active successional dynamics (e. g., toward oak or pine-oak forests at low to mid altitudes). Enrichment planting will be required to overcome seed limitation, especially in plantations far from natural forests. We conclude that plantations should be perceived as dynamic systems where successional trajectories and diversity levels are determined by abiotic constraints, complex balances of competitive and facilitative interactions, the spatial configuration of native seed sources, and species life-history traits.
The following values have no corresponding Zotero field: pub-location: 1990 M STREET NW, STE 700, WASHINGTON, DC 20036 USA publisher: ECOLOGICAL SOC AMER
Keywords: competition; environmental gradients; Facilitation; management strategy; Mediterranean forests; pine plantations; Regeneration; seed dispersal; species diversity; stand density

Intraspecific competition and water use efficiency in Quercus suber: evidence of an optimum tree density? - Gouveia, António C; Freitas, Helena (Trees, 2008)
The dehesa and montado agroecosystems seem to be water-stress induced structures and some authors have found evidence of a relationship between stand tree density and mean annual precipitation. In order to assess the ecophysiological responses of Quercus suber to increasing tree density and to evaluate if there was evidence of an ‘‘optimum tree density’’ with respect to mean annual rainfall in our study area, we established a tree-density gradient of 20, 40, and 60 trees ha -1 , coded D20, D40, and D60, respectively. Trees in D40 plots had higher speciﬁc leaf area (SLA) values and the highest water content. Both D20 and D60 trees had leaves with higher dry matter content (LDMC). The trade-off between SLA and LDMC was very strong and placed D40 trees as the least stressed, in terms of leaf anatomy. We also found differences in mean carbon isotope discrimination (D), between different density plots, as big as 1.25%. Again, D40 trees discriminated more against 13 C than the trees from D20 and D60 plots, which suggests a less conservative water use strategy, possibly deriving from greater water availability. The lower water retention in the D20 areas and the increased competition for water resources in D60 plots placed trees, in both areas, in a more stressful situation, regarding water availability. The D40 areas thus seemed to represent a more favourable environment for Q. suber in our montado. Therefore, the areas with 40 trees ha -1 suggest the existence of an optimum tree density with respect to annual rainfall in our site, and may represent a compromise between an increased retention of water resources and intraspeciﬁc competition.
Keywords: carbon isotope discrimination; evergreen oak; montado; Specific leaf area; stand density

Sensitivity of volatile monoterpene emission to changes in canopy structure: a model-based exercise with a process-based emission model - Grote, Rüdiger (New Phytologist, 2007)
* • This paper investigates the dependence of monoterpene emissions at the canopy scale on total leaf area and leaf distribution. Simulations were carried out for a range of hypothetical but realistic forest canopies of the evergreen Quercus ilex (holm oak). * • Two emission models were applied that either did (SIM-BIM2) or did not (G93) account for cumulative responses to temperature and light. Both were embedded into a canopy model that considered spatial and temporal variations of foliage properties. This canopy model was coupled to a canopy climate model (CANOAK) to determine the micrometeorological conditions at the leaf scale. * • Structural properties considerably impacted monoterpene emission. The sensitivities to changes in total leaf area and to leaf area distribution were found to be of similar magnitude. The two different models performed similarly on a whole-year basis but showed clear differences during certain episodes. * • The analysis showed that structural indices have to be carefully evaluated for proper scaling of emission from leaves to canopy. Further research is encouraged on seasonal dynamics of emission potentials.
Keywords: Biological; biomass; foliage distribution; leaf area index; light; Models; monoterpene emission; Monoterpenes; Monoterpenes: metabolism; photosynthesis; Photosynthesis: radiation effects; Plant Leaves; Plant Leaves: metabolism; Plant Leaves: radiation effects; Quercus; Quercus ilex; Quercus: metabolism; Quercus: radiation effects; Scaling; stand density; Temperature; Time Factors; Volatilization

Relación entre la densidad de la masa y la producción de corcho en montes alcornocales del sur de españa - Álvarez, E. Torres; González, G. Montero; Suárez, M. A.; Cámara, D. E. L. A.; TORRES ÁLVAREZ, E.; Montero González, G.; Suárez de la Cámara, M. A. (II Congreso Forestal Español, 1997)
In this paper the influence of cork-oak stand density on quantity and quality cork production is studied. Seventy five experimental plots were installed at Cortes de la Frontera (Málaga, Spain) cork-oak forests. Sorne stand and productive variables for different basal area were studied. The statistical analysis of the data permit to propose 20-25 m2!ha basal area as the optimum stand density
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: cork-oak; Quercus suber; silviculture; stand density

Relación entre la densidad de la masa y la producción de corcho en montes alcornocales del sur de españa - Álvarez, E Torres; González, G Montero; Suárez, M A; Cámara, D E L A; Torres Álvarez, E; Montero González, G; Suárez de la Cámara, M A (II Congreso Forestal Español, 1997)
In this paper the influence of cork-oak stand density on quantity and quality cork production is studied. Seventy five experimental plots were installed at Cortes de la Frontera (Málaga, Spain) cork-oak forests. Sorne stand and productive variables for different basal area were studied. The statistical analysis of the data permit to propose 20-25 m2!ha basal area as the optimum stand density
Keywords: cork-oak; Quercus suber; silviculture; stand density

INFLUENCIA DE LA DENSIDAD DE LA MASA EN LA CALIDAD Y PRODUCCION DE CORCHO EN LOS ALCORNOCALES DE CORTES DE LA FRONTERA (MALAGA) - Montero, G; TORRES, E; Suárez, M A; Ortega, C (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
The influence of stand density on cork yield was evaluated for the Cortes de la Frontera (Spain) cork oak stand. Fifty five experimental plots were installed. The modular values of several variables which define cork oak yield potential of a tree, are presented by stand densitY'clusters (basal area groups). Likewise, many stand variables for different basal areas were studied
Keywords: cork-oak; silviculture; stand density